Classifications of the Last Emirs of Bukhara in the Works of Local Historians (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
this article contains the works of a number of historians analyzed, the valuable information about the last emirs of Bukhara presented in their works was summarized, systematized from the oint of view of history, and opinions were given about their reliability and content. Scientific information about the country, socio-economic status, and specific characteristics of the emirs has been presented.